Analysis of The Effect of Working Capital Management on Profitability In Manufacturing Companies In Indonesia - Ahmad, Putri; Ningsih, Angelya; Sitorus, Natalia; Sucipto, Tia (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of working capital management on profitability in manufacturing companies in Indonesia. The method employed is a literature review by examining five related scientific journals. The findings indicate that efficient working capital management, particularly through the management of the Cash Conversion Cycle (CCC), has a positive impact on company profitability. Components such as receivables, inventory, and payables management play a crucial role in enhancing operational efficiency and liquidity, ultimately leading to improved profitability. Optimal working capital management enables companies to maximize Return on Assets (ROA) as an indicator of financial performance efficiency. These findings provide insights for companies to improve working capital management to achieve financial stability and sustainability.